Designing UI/UX Thrift shop Website Using User Centered Design (UCD) Method (Case Study: Backfold Market) - Bachtiar Firmansyah; Dedi I. Inan; Ratna Juita; Marlinda Sanglise (G-Tech: Jurnal Teknologi Terapan, 2024)
Backfold Market, a business currently relying on conventional sales and social media, recognizes the need for technological advancement. To address this, they aim to establish a sales platform in the form of a website. This website will serve as a marketplace for second-brand clothes from renowned brands. The user centered design (UCD) method guides the development of the user interface and user experience. By focusing on users at every stage, the UCD method ensures that each design aligns with user needs. Through interviews identifies user goals and desires, translating them into requirements and features. The resulting designs and prototypes are evaluated using the Maze.design application, achieving an impressive average usability score of 97. This score indicates that the website’s interface design is user-friendly and easy to navigate for its audience.